Severe Hemolytic Anemia Associated with Mild Pneumonia Caused by Mycoplasma pneumonia - Zafer Kurugol; Serife Sebnem Onen; Guldane Koturoglu (Case Reports in Medicine)
We report a case of M. pneumoniae infection presenting with severe hemolytic anemia in a 4-year-old girl, with a ten-day history of paleness, weakness, and nonproductive cough. She was very pale and tachycardic. However, she was not tachypneic. Chest examination showed normal breath sounds. No rhoncus or whistling was heard. As the erythrocyte sedimentation rate was excessively elevated, the differential diagnosis primarily comprised hematological malignancies. Direct Coombs' test was positive. Diagnosis of M. pneumoniae infection was confirmed by elevated levels of M. pneumoniae IgG and IgM antibodies and a chest X-ray suggestive of atypical pneumonia. The patient was treated with clarithromycin and packed red cell transfusion and showed a favorable recovery within ten days after admission. In conclusion, this case demonstrates that severe hemolytic anemia caused by M. pneumoniae is not always associated with severe pulmonary involvement, even when the respiratory infection is very mild, M. pneumoniae may be the cause of severe anemia.